A polyurethane material for spraying and plugging air leakage in coal mines and its preparation method

By adding wrinkled graphene oxide to coat UiO-66-NH2/modified multi-wall carbon nanotubes in coal mines, the problem of poor safety of existing materials in coal mines is solved, and the flame retardant, mechanical and foaming properties of the materials are significantly improved.

CN119505147BActive Publication Date: 2025-04-15INNER MONGOLIA JINGRUN MINING SAFETY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411754265.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-15
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing coal mine spraying and leak-blocking air plugging materials lack excellent flame retardant, anti-combustible human poisoning and electricity protection, resulting in poor safety when used in coal mines.

Method used

By adding the obtained wrinkled graphene oxide to coat UiO-66-NH2/modified multi-wall carbon nanotubes, the mechanical properties, flame retardant properties and foaming multiples of the polyurethane material for spraying and plugging air in coal mines are significantly improved.

Benefits of technology

It significantly improves the flame retardant properties, mechanical properties and foaming multiples of the material, improves the microstructure of the material, and enhances its safety and effectiveness in coal mine applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165844180000131
    Figure BDA0005165844180000131
  • Figure BDA0005165844180000141
    Figure BDA0005165844180000141
Patent Text Reader

Abstract

The present invention proposes a polyurethane material for spraying and plugging air leakage in coal mines and a preparation method thereof, and belongs to the technical field of polyurethane. After pre-treatment of multi-walled carbon nanotubes, coupling phytic acid and silane coupling agent, reacting with UiO‑66‑NH2, surface-coated graphene oxide layer, mixed with polyether polyol, catalyst, antistatic agent, added to water, adding foaming agent and silicone oil, heating and stirring mixing, transferred to a mold, adding diisocyanate, after foaming is completed and the temperature of the material is reduced to room temperature, drying, heating and aging, and preparing a polyurethane material for spraying and plugging air leakage in coal mines. The present invention can significantly improve the mechanical properties and strength of the polyurethane material for spraying and plugging air leakage in coal mines by adding the obtained wrinkled graphene oxide coated UiO‑66‑NH2 / modified multi-walled carbon nanotubes, and also significantly improve the flame retardant properties of the material such as oxygen index, improve the foaming multiple to a certain extent, the preparation method is simple, can significantly improve the flame retardant and mechanical properties, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane, and in particular to a polyurethane material for spraying and plugging air leakage in coal mines and a preparation method thereof. Background Art

[0002] A gas outburst accident refers to an accident caused by a geological disaster in which, as the depth of coal mining increases and the gas content increases, the weak coal seam breaks through the resistance line under the action of ground stress and the gravitational force of gas release, instantly releasing a large amount of gas and coal.

[0003] Wall plugging as a major measure to prevent and control gas disasters has attracted in-depth research from many scholars. Gas plugging materials are sprayed on the walls of coal mine tunnels, and the gas leakage channels on the tunnel surface are blocked by "plugging". Combined with the gas extraction process in the coal mine wall, it can not only effectively prevent the gas outflow in the tunnel and ensure the safe and efficient underground mining of coal mines, but also increase the gas concentration in the coal seam to facilitate extraction and utilization, thereby greatly improving the coal mine production capacity.

[0004] Chinese invention patent CN104909636B records that "it includes a fast-setting expansion material, a microcapsule containing a healing agent, and a catalyst. Among them, the fast-setting expansion material includes cement clinker, fly ash, steel slag, stone powder, salt mud, carbide slag, expansion agent, water reducer, and sand. The microcapsule is composed of a wall material (polymer resin) and a core material (healing agent); the wall material of the microcapsule is at least one of urea-formaldehyde resin, melamine formaldehyde resin, melamine urea-formaldehyde resin and polyurethane, and the healing agent is a polyurethane prepolymer, isocyanate, phenolic resin , epoxy resin, styrene, acrylates, dicyclopentadiene (DCPD) and other olefins containing double bonds, and the catalyst is at least one of Grubbs catalyst, dibutyltin dilaurate and amines. It has the advantages of automatic detection, automatic healing, moderate expansion, rapid coagulation, good conveyability, strong consolidation, green environmental protection and low price. Although the above patent can achieve the blocking effect, it lacks excellent flame retardant and anti-burning and human poisoning functions, and also lacks anti-electric effects. It is used in coal mines and has poor safety.

[0005] Chinese invention patent CN103388486B records that "2%-6% polyvinyl alcohol, 1%-5% phosphoric acid, and 1%-5% urea are reacted and polymerized in water solvent, and then 4%-10% white latex and 2%-6% melamine are added to continue the reaction, and then 15%-25% inorganic aggregate is added and fully stirred and mixed to finally obtain the product. The inorganic aggregate is any combination of talcum powder, kaolin, and mica powder. The material has strong wall adhesion and can be conveniently sprayed on the surface of coal body and windbreak belt; it has good flame retardant and anti-chemical properties, The expanded carbonized layer formed is thicker than the original uncarbonized thickness, and during combustion, carbonization occurs only in the place in direct contact with the flame, and the flame will not extend. The construction performance is good, and spraying equipment can be used for spraying application. Although the provided plugging material has flame retardant function, it only relies on the inherent characteristics of polyvinyl alcohol and ammonium polyphosphate raw materials for flame retardancy, and the inorganic aggregate used is not modified, so that the provided plugging material has poor flame retardant effect, and lacks excellent tensile strength and anti-electricity effects.

[0006] In summary, the development of a flame retardant coal mine spray plugging air leakage material is a key issue that needs to be urgently addressed in the field of plugging material technology. Summary of the invention

[0007] The purpose of the present invention is to provide a polyurethane material for coal mine spray plugging air leakage and a preparation method thereof. By adding the prepared wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, the mechanical properties and strength of the prepared polyurethane material for coal mine spray plugging air leakage can be significantly improved, and the flame retardant properties of the material such as the oxygen index are also significantly improved, and the foaming multiple can also be improved to a certain extent. The preparation method is simple, and the flame retardant and mechanical properties can be significantly improved, and the material has broad application prospects.

[0008] The technical solution of the present invention is achieved in this way:

[0009] The invention provides a preparation method of a polyurethane material for coal mine spray plugging air leakage. The method comprises the following steps: pretreating multi-walled carbon nanotubes, coupling phytic acid and a silane coupling agent, reacting with UiO-66-NH2, coating a surface with a graphene oxide layer, mixing with a polyether polyol, a catalyst and an antistatic agent, adding the mixture into water, adding a foaming agent and silicone oil, heating and stirring the mixture, transferring the mixture into a mold, adding diisocyanate, drying after foaming is completed and the temperature of the material is reduced to room temperature, heating and maturing, and preparing the polyurethane material for coal mine spray plugging air leakage.

[0010] As a further improvement of the present invention, the following steps are included:

[0011] S1. adding multi-walled carbon nanotubes to nitric acid, heating to reflux with stirring for reaction, centrifuging, washing, and drying to obtain pretreated multi-walled carbon nanotubes;

[0012] S2. adding the pretreated multi-walled carbon nanotubes to water, adding phytic acid and sodium dihydrogen phosphate, hydrothermal reaction, centrifugation, washing, solid drying, adding to ethanol, adding a composite silane coupling agent, heating and stirring the reaction, centrifugation, washing, and drying to obtain modified multi-walled carbon nanotubes;

[0013] S3. Dissolving zirconium tetrachloride and 2-aminoterephthalic acid in N,N-dimethylformamide to obtain a precursor solution, adding the modified multi-walled carbon nanotubes, heating and stirring the reaction, centrifuging, washing, and drying to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0014] S4. The UiO-66-NH2 / modified multi-walled carbon nanotubes were added to the graphene oxide aqueous dispersion and spray dried to obtain wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0015] S5. Mix polyether polyol, wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, catalyst, and antistatic agent and add them into water, add foaming agent and silicone oil, heat and stir to mix, transfer into a mold, add diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat and mature to obtain a polyurethane material for spraying and plugging air leaks in coal mines.

[0016] As a further improvement of the present invention, the concentration of nitric acid in step S1 is 2-3 mol / L, and the heating reflux stirring reaction time is 4-6 h.

[0017] As a further improvement of the present invention, the mass ratio of the pretreated multi-walled carbon nanotubes, phytic acid, sodium dihydrogen phosphate and composite silane coupling agent in step S2 is 10:3-4:1-2:4-5, the temperature of the hydrothermal reaction is 140-150°C, the time is 2-4h, the composite silane coupling agent is selected from at least one of KH550, KH560, KH570, KH580, KH590, KH602, and KH792, and the temperature of the heating and stirring reaction is 35-45°C, and the time is 2-4h.

[0018] As a further improvement of the present invention, the composite silane coupling agent is a mixture of KH560 and KH792, with a mass ratio of 3-5:2-4.

[0019] As a further improvement of the present invention, in step S3, the mass ratio of zirconium tetrachloride, 2-aminoterephthalic acid and modified multi-walled carbon nanotubes is 4:2-3:5-7, and the temperature of the heating and stirring reaction is 120-130° C. and the time is 20-24 hours.

[0020] As a further improvement of the present invention, the solid-liquid ratio of the UiO-66-NH2 / modified multi-walled carbon nanotubes and graphene oxide aqueous dispersion in step S4 is 1:3-5 g / mL, and the concentration of the graphene oxide aqueous dispersion is 0.1-0.5 mg / mL.

[0021] As a further improvement of the present invention, the mass ratio of the polyether polyol, wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, catalyst, antistatic agent, foaming agent, silicone oil and diisocyanate in step S5 is 10:2-3:0.01-0.015:0.2-0.5:1.5-2:1-2:9-11, the temperature of heating, stirring and mixing is 50-60°C, the temperature of heating and aging is 110-130°C, and the time is 3-5h.

[0022] As a further improvement of the present invention, the polyether polyol is selected from at least one of bisphenol A diethanol ether, polytrimethylene ether glycol, polytetramethylene glycol, tetramethylene oxide copolymer glycol, and polyoxypropylene glycol, the catalyst is a Raney nickel catalyst, the foaming agent is n-hexane, the diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, aliphatic isocyanate, naphthalene 1,5-diisocyanate, xylene diisocyanate, and tetramethyl-m-xylene diisocyanate, and the antistatic agent is carbon black.

[0023] The present invention further protects a polyurethane material for spraying and plugging air leakage in coal mines, which is prepared by the above-mentioned preparation method.

[0024] The present invention has the following beneficial effects:

[0025] The present invention can significantly improve the mechanical properties and strength of the prepared polyurethane material for coal mine spray plugging air leakage by adding the prepared wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, and also significantly improve the flame retardant properties of the material such as the oxygen index, and can also improve the foaming multiple to a certain extent. The preparation method is simple, can significantly improve the flame retardant and mechanical properties, and has broad application prospects.

[0026] Carbon nanotubes can form solid-state entangled nanotube bundles with extremely complex structures. Carbon nanotubes can be used as a flame retardant because of their high thermal conductivity and can promote the formation of a carbon layer during combustion, protecting the polymer from further degradation. However, carbon nanotubes have poor dispersibility in both organic and aqueous solutions, and poor compatibility with polymer materials.

[0027] The present invention prepares wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, takes carbon nanotubes as carriers, and after nitric acid pretreatment, the surfaces of the carbon nanotubes have hydroxyl groups, which can be coupled with phytic acid, and can be connected with a silane coupling agent (the composite silane coupling agent is a mixture of KH560 and KH792), so that the prepared modified multi-walled carbon nanotubes have phosphate, amino, double bonds, and epoxy groups, which improves the flame retardant effect on the one hand, and provides feasibility for subsequent reactions on the other hand.

[0028] The amino group of UiO-66-NH2 of the present invention can undergo a ring-opening coupling reaction with the epoxy group of the modified multi-walled carbon nanotube, thereby preparing UiO-66-NH2 / modified multi-walled carbon nanotube, UiO-66-NH2 improves mechanical properties and antistatic properties, and then under the coating effect of graphene oxide, wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotube is prepared, and wrinkling improves the compatibility of the material with the polyurethane material on the one hand, and at the same time, the hydroxyl group and the amino group on the wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotube can also participate in the chain reaction of the polyurethane, further improving the dispersibility in the matrix material, so that its mechanical properties are not affected, and the antistatic property of the material is also improved to a certain extent. The crumpled graphene oxide coated UiO-66-NH2 / modified multi-walled carbon nanotubes carry multiple flame retardant elements such as phosphorus, nitrogen, and silicon, and greatly improve the flame retardant properties of the polyurethane material through a multi-effect synergistic method. In addition, the crumpled graphene oxide coated UiO-66-NH2 / modified multi-walled carbon nanotubes improve the microstructure of the material while improving the flame retardant properties of the polyurethane, reducing the size of the micropores inside the material, thereby improving the tensile strength and compressive strength of the composite material. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Graphene oxide, purity >99%, thickness <5 nm, oxygen content 33-37%, was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0031] Example 1

[0032] This embodiment provides a method for preparing a polyurethane material for spraying and plugging air leakage in coal mines, comprising the following steps:

[0033] S1. 10 g of multi-walled carbon nanotubes were added to 200 mL of 2 mol / L nitric acid, heated under reflux for 4 h, centrifuged, washed, and dried to obtain pretreated multi-walled carbon nanotubes;

[0034] S2. 10 g of pretreated multi-walled carbon nanotubes were added to 200 mL of water, 3 g of phytic acid and 1 g of sodium dihydrogen phosphate were added, and the reaction was carried out at 140 ° C for 2 h, centrifuged, washed, and the solid was dried. Then, the solid was added to 200 mL of ethanol, 4 g of a composite silane coupling agent was added, and the mixture was heated to 35 ° C. The reaction was stirred for 2 h, centrifuged, washed, and dried to obtain modified multi-walled carbon nanotubes;

[0035] The composite silane coupling agent is a mixture of KH560 and KH792, with a mass ratio of 3:2;

[0036] S3. 4 g zirconium tetrachloride and 2 g 2-aminoterephthalic acid were dissolved in 200 mL N, N-dimethylformamide to obtain a precursor solution, 5 g modified multi-walled carbon nanotubes were added, heated to 120 ° C, stirred for 20 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0037] S4. 10 g UiO-66-NH2 / modified multi-walled carbon nanotubes were added to 30 mL 0.1 mg / mL graphene oxide aqueous dispersion and spray dried to obtain wrinkled graphene oxide coated UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0038] S5. Mix 10g of bisphenol A diethanol ether, 2g of wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, 0.01g of Raney nickel catalyst, and 0.2g of carbon black into 200mL of water, add 1.5g of n-hexane and 1g of silicone oil, heat to 50°C, stir and mix for 30s, transfer into a mold, add 9g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 110°C, and mature for 3h to obtain a polyurethane material for spray plugging air leakage in coal mines.

[0039] Example 2

[0040] This embodiment provides a method for preparing a polyurethane material for spraying and plugging air leakage in coal mines, comprising the following steps:

[0041] S1. 10 g of multi-walled carbon nanotubes were added to 200 mL of 3 mol / L nitric acid, heated under reflux for 6 h, centrifuged, washed, and dried to obtain pretreated multi-walled carbon nanotubes;

[0042] S2. 10 g of pretreated multi-walled carbon nanotubes were added to 200 mL of water, 4 g of phytic acid and 2 g of sodium dihydrogen phosphate were added, and the reaction was carried out at 150 ° C for 4 h, centrifuged, washed, and the solid was dried. Then, the mixture was added to 200 mL of ethanol, 5 g of a composite silane coupling agent was added, and the mixture was heated to 45 ° C. The reaction was stirred for 4 h, centrifuged, washed, and dried to obtain modified multi-walled carbon nanotubes;

[0043] The composite silane coupling agent is a mixture of KH560 and KH792, with a mass ratio of 5:4;

[0044] S3. 4 g zirconium tetrachloride and 3 g 2-aminoterephthalic acid were dissolved in 200 mL N, N-dimethylformamide to obtain a precursor solution, 7 g modified multi-walled carbon nanotubes were added, heated to 130 ° C, stirred for 24 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0045] S4. 10 g UiO-66-NH2 / modified multi-walled carbon nanotubes were added to 50 mL of 0.5 mg / mL graphene oxide aqueous dispersion and spray dried to obtain wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0046] S5. Mix 10g of bisphenol A diethanol ether, 3g of wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, 0.015g of Raney nickel catalyst, and 0.5g of carbon black into 200mL of water, add 2g of n-hexane and 2g of silicone oil, heat to 60°C, stir and mix for 30s, transfer into a mold, add 11g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 130°C, and mature for 5h to obtain a polyurethane material for spray plugging air leakage in coal mines.

[0047] Example 3

[0048] This embodiment provides a method for preparing a polyurethane material for spraying and plugging air leakage in coal mines, comprising the following steps:

[0049] S1. 10 g of multi-walled carbon nanotubes were added to 200 mL of 2.5 mol / L nitric acid, heated under reflux for 5 h, centrifuged, washed, and dried to obtain pretreated multi-walled carbon nanotubes;

[0050] S2. 10 g of pretreated multi-walled carbon nanotubes were added to 200 mL of water, 3.4 g of phytic acid and 1.5 g of sodium dihydrogen phosphate were added, and the reaction was carried out at 145 ° C for 3 h, centrifuged, washed, and the solid was dried. Then, the mixture was added to 200 mL of ethanol, 4.6 g of a composite silane coupling agent was added, and the mixture was heated to 40 ° C. The reaction was stirred for 3 h, centrifuged, washed, and dried to obtain modified multi-walled carbon nanotubes;

[0051] The composite silane coupling agent is a mixture of KH560 and KH792, with a mass ratio of 4:3;

[0052] S3. 4 g zirconium tetrachloride and 2.7 g 2-aminoterephthalic acid were dissolved in 200 mL N, N-dimethylformamide to obtain a precursor solution, 6 g modified multi-walled carbon nanotubes were added, heated to 125 ° C, stirred for 22 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0053] S4. 10 g UiO-66-NH2 / modified multi-walled carbon nanotubes were added to 40 mL 0.3 mg / mL graphene oxide aqueous dispersion and spray dried to obtain wrinkled graphene oxide coated UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0054] S5. Mix 10g of bisphenol A diethanol ether, 2.5g of wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, 0.012g of Raney nickel catalyst, and 0.35g of carbon black into 200mL of water, add 1.7g of n-hexane and 1.5g of silicone oil, heat to 55°C, stir and mix for 30s, transfer into a mold, add 10g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 120°C, and mature for 4h to obtain a polyurethane material for spray plugging air leakage in coal mines.

[0055] Example 4

[0056] Compared with Example 3, the difference is that the composite silane coupling agent is a single KH560.

[0057] Example 5

[0058] Compared with Example 3, the difference is that the composite silane coupling agent is a single KH792.

[0059] Comparative Example 1

[0060] Compared with Example 3, the difference is that no composite silane coupling agent is added in step S2.

[0061] The details are as follows:

[0062] S1. 10 g of multi-walled carbon nanotubes were added to 200 mL of 2.5 mol / L nitric acid, heated under reflux for 5 h, centrifuged, washed, and dried to obtain pretreated multi-walled carbon nanotubes;

[0063] S2. 10 g of pretreated multi-walled carbon nanotubes were added to 200 mL of water, 3.4 g of phytic acid and 1.5 g of sodium dihydrogen phosphate were added, and the reaction was hydrothermally reacted at 145 ° C for 3 h, centrifuged, washed, and the solid was dried to obtain modified multi-walled carbon nanotubes;

[0064] S3. 4 g zirconium tetrachloride and 2.7 g 2-aminoterephthalic acid were dissolved in 200 mL N, N-dimethylformamide to obtain a precursor solution, 6 g modified multi-walled carbon nanotubes were added, heated to 125 ° C, stirred for 22 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0065] S4. 10 g UiO-66-NH2 / modified multi-walled carbon nanotubes were added to 40 mL 0.3 mg / mL graphene oxide aqueous dispersion and spray dried to obtain wrinkled graphene oxide coated UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0066] S5. Mix 10g of bisphenol A diethanol ether, 2.5g of wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, 0.012g of Raney nickel catalyst, and 0.35g of carbon black into 200mL of water, add 1.7g of n-hexane and 1.5g of silicone oil, heat to 55°C, stir and mix for 30s, transfer into a mold, add 10g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 120°C, and mature for 4h to obtain a polyurethane material for spray plugging air leakage in coal mines.

[0067] Comparative Example 2

[0068] Compared with Example 3, the difference is that phytic acid is not added in step S2.

[0069] The details are as follows:

[0070] S1. 10 g of multi-walled carbon nanotubes were added to 200 mL of 2.5 mol / L nitric acid, heated under reflux for 5 h, centrifuged, washed, and dried to obtain pretreated multi-walled carbon nanotubes;

[0071] S2. 10 g of pretreated multi-walled carbon nanotubes were added to 200 mL of ethanol, 4.6 g of a composite silane coupling agent was added, heated to 40 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified multi-walled carbon nanotubes;

[0072] The composite silane coupling agent is a mixture of KH560 and KH792, with a mass ratio of 4:3;

[0073] S3. 4 g zirconium tetrachloride and 2.7 g 2-aminoterephthalic acid were dissolved in 200 mL N, N-dimethylformamide to obtain a precursor solution, 6 g modified multi-walled carbon nanotubes were added, heated to 125 ° C, stirred for 22 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0074] S4. 10 g UiO-66-NH2 / modified multi-walled carbon nanotubes were added to 40 mL 0.3 mg / mL graphene oxide aqueous dispersion and spray dried to obtain wrinkled graphene oxide coated UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0075] S5. Mix 10g of bisphenol A diethanol ether, 2.5g of wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, 0.012g of Raney nickel catalyst, and 0.35g of carbon black into 200mL of water, add 1.7g of n-hexane and 1.5g of silicone oil, heat to 55°C, stir and mix for 30s, transfer into a mold, add 10g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 120°C, and mature for 4h to obtain a polyurethane material for spray plugging air leakage in coal mines.

[0076] Comparative Example 3

[0077] Compared with Example 3, the difference is that step S3 is not performed.

[0078] The details are as follows:

[0079] S1. 10 g of multi-walled carbon nanotubes were added to 200 mL of 2.5 mol / L nitric acid, heated under reflux for 5 h, centrifuged, washed, and dried to obtain pretreated multi-walled carbon nanotubes;

[0080] S2. 10 g of pretreated multi-walled carbon nanotubes were added to 200 mL of water, 3.4 g of phytic acid and 1.5 g of sodium dihydrogen phosphate were added, and the reaction was carried out at 145 ° C for 3 h, centrifuged, washed, and the solid was dried. Then, the mixture was added to 200 mL of ethanol, 4.6 g of a composite silane coupling agent was added, and the mixture was heated to 40 ° C. The reaction was stirred for 3 h, centrifuged, washed, and dried to obtain modified multi-walled carbon nanotubes;

[0081] The composite silane coupling agent is a mixture of KH560 and KH792, with a mass ratio of 4:3;

[0082] S3. 10 g of modified multi-walled carbon nanotubes were added to 40 mL of 0.3 mg / mL aqueous dispersion of graphene oxide and spray dried to obtain wrinkled graphene oxide-coated modified multi-walled carbon nanotubes;

[0083] S4. Mix 10g of bisphenol A diethanol ether, 2.5g of wrinkled graphene oxide-coated modified multi-walled carbon nanotubes, 0.012g of Raney nickel catalyst, and 0.35g of carbon black into 200mL of water, add 1.7g of n-hexane and 1.5g of silicone oil, heat to 55°C, stir and mix for 30s, transfer into a mold, add 10g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 120°C, and mature for 4h to obtain the polyurethane material for spray plugging air leakage in coal mines.

[0084] Comparative Example 4

[0085] Compared with Example 3, the difference is that step S4 is not performed.

[0086] The details are as follows:

[0087] S1. 10 g of multi-walled carbon nanotubes were added to 200 mL of 2.5 mol / L nitric acid, heated under reflux for 5 h, centrifuged, washed, and dried to obtain pretreated multi-walled carbon nanotubes;

[0088] S2. 10 g of pretreated multi-walled carbon nanotubes were added to 200 mL of water, 3.4 g of phytic acid and 1.5 g of sodium dihydrogen phosphate were added, and the reaction was carried out at 145 ° C for 3 h, centrifuged, washed, and the solid was dried. Then, the mixture was added to 200 mL of ethanol, 4.6 g of a composite silane coupling agent was added, and the mixture was heated to 40 ° C. The reaction was stirred for 3 h, centrifuged, washed, and dried to obtain modified multi-walled carbon nanotubes;

[0089] The composite silane coupling agent is a mixture of KH560 and KH792, with a mass ratio of 4:3;

[0090] S3. 4 g zirconium tetrachloride and 2.7 g 2-aminoterephthalic acid were dissolved in 200 mL N, N-dimethylformamide to obtain a precursor solution, 6 g modified multi-walled carbon nanotubes were added, heated to 125 ° C, stirred for 22 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes;

[0091] S4. Mix 10g of bisphenol A diethanol ether, 2.5g of UiO-66-NH2 / modified multi-walled carbon nanotubes, 0.012g of Raney nickel catalyst, and 0.35g of carbon black into 200mL of water, add 1.7g of n-hexane and 1.5g of silicone oil, heat to 55°C, stir and mix for 30s, transfer into a mold, add 10g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 120°C, and mature for 4h to obtain a polyurethane material for spraying and plugging air leaks in coal mines.

[0092] Comparative Example 5

[0093] Compared with Example 3, the difference is that wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes are not added in step S5.

[0094] The details are as follows:

[0095] Mix 10g of bisphenol A diethanol ether, 0.012g of Raney nickel catalyst, and 0.35g of carbon black into 200mL of water, add 1.7g of n-hexane and 1.5g of silicone oil, heat to 55°C, stir and mix for 30s, transfer into a mold, add 10g of diphenylmethane diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat to 120°C, and mature for 4h to obtain a polyurethane material for spray plugging air leakage in coal mines.

[0096] Test Example 1

[0097] The flame retardant properties of the polyurethane materials for spraying and plugging air leakage in coal mines prepared in Examples 1-5 and Comparative Examples 1-5 were tested, and the results are shown in Table 1.

[0098] 1. Limiting oxygen index (LOI) test

[0099] According to GB / T2406.2-2009 standard, the sample was made into a shape with a length, width and thickness of 100mm×6.5mm×2mm respectively, and the sample was tested using an HC-2 oxygen index meter.

[0100] 2. Vertical burning (UL94) test

[0101] According to GB / T2408-2021 standard, the shape with dimensions of 100mm×12.7mm×2mm was made, and the samples were tested using CZF-3 horizontal and vertical measuring instrument.

[0102] Table 1

[0103] Group LOI(%) Flame retardant grade Example 1 33.2 V-0 Example 2 33.5 V-0 Example 3 33.9 V-0 Example 4 27.3 V-1 Example 5 29.8 V-0 Comparative Example 1 25.8 V-1 Comparative Example 2 28.7 V-1 Comparative Example 3 30.5 V-0 Comparative Example 4 31.5 V-0 Comparative Example 5 22.9 V-2

[0104] It can be seen from the above table that the polyurethane materials for coal mine spray plugging air leakage prepared in Examples 1-3 of the present invention have good flame retardancy.

[0105] Test Example 2

[0106] The flame retardant properties of the polyurethane materials for spraying and plugging air leakage in coal mines prepared in Examples 1-5 and Comparative Examples 1-5 were tested, and the results are shown in Table 2.

[0107] The tensile strength properties of each group of materials were determined according to the test method in GB / T 9641-1988, and the sample tensile speed was 5 mm / min.

[0108] Table 2

[0109] Group Tensile strength(kPa) Example 1 295 Example 2 299 Example 3 302 Example 4 234 Example 5 265 Comparative Example 1 217 Comparative Example 2 280 Comparative Example 3 244 Comparative Example 4 258 Comparative Example 5 154

[0110] It can be seen from the above table that the polyurethane materials for coal mine spray plugging air leakage prepared in Examples 1-3 of the present invention have good mechanical properties.

[0111] Test Example 3

[0112] The surface resistance of the polyurethane materials for spraying and plugging air leakage in coal mines prepared in Examples 1-5 and Comparative Examples 1-5 was tested, and the results are shown in Table 3.

[0113] The surface resistance of each group of materials was determined according to the surface resistance method in MT / T 113-1995.

[0114] Table 3

[0115]

[0116]

[0117] It can be seen from the above table that the polyurethane materials for coal mine spray plugging air leakage prepared in Examples 1-3 of the present invention have a good surface resistance.

[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyurethane material for spraying and plugging air leakage in coal mines, characterized in that: The following steps are involved: S1. adding multi-walled carbon nanotubes to nitric acid, heating to reflux with stirring for reaction, centrifuging, washing, and drying to obtain pretreated multi-walled carbon nanotubes; S2. Add the pretreated multi-walled carbon nanotubes to water, add phytic acid and sodium dihydrogen phosphate, hydrothermally react, centrifuge, wash, dry the solid, add to ethanol, add a composite silane coupling agent, heat and stir to react, centrifuge, wash, and dry to obtain modified multi-walled carbon nanotubes; the composite silane coupling agent is a mixture of KH560 and KH792 in a mass ratio of 3-5:2-4; S3. Dissolving zirconium tetrachloride and 2-aminoterephthalic acid in N,N-dimethylformamide to obtain a precursor solution, adding the modified multi-walled carbon nanotubes, heating and stirring the reaction, centrifuging, washing, and drying to obtain UiO-66-NH2 / modified multi-walled carbon nanotubes; S4. The UiO-66-NH2 / modified multi-walled carbon nanotubes were added to the graphene oxide aqueous dispersion and spray dried to obtain wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes; S5. Mix polyether polyol, wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, catalyst, and antistatic agent and add them into water, add foaming agent and silicone oil, heat and stir to mix, transfer into a mold, add diisocyanate, and after foaming is completed and the temperature of the material drops to room temperature, dry, heat and mature to obtain a polyurethane material for spraying and plugging air leaks in coal mines.

2. The preparation method according to claim 1, characterized in that: The concentration of nitric acid in step S1 is 2-3 mol / L, and the heating reflux stirring reaction time is 4-6 h.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the pretreated multi-walled carbon nanotubes, phytic acid, sodium dihydrogen phosphate and composite silane coupling agent in step S2 is 10:3-4:1-2:4-5, the temperature of the hydrothermal reaction is 140-150°C, the time is 2-4h, and the temperature of the heating and stirring reaction is 35-45°C, and the time is 2-4h.

4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of zirconium tetrachloride, 2-aminoterephthalic acid and modified multi-walled carbon nanotubes is 4:2-3:5-7, and the temperature of the heating and stirring reaction is 120-130° C. and the time is 20-24 hours.

5. The preparation method according to claim 1, characterized in that: The solid-liquid ratio of the UiO-66-NH2 / modified multi-walled carbon nanotubes and graphene oxide aqueous dispersion in step S4 is 1:3-5 g / mL, and the concentration of the graphene oxide aqueous dispersion is 0.1-0.5 mg / mL.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the polyether polyol, wrinkled graphene oxide-coated UiO-66-NH2 / modified multi-walled carbon nanotubes, catalyst, antistatic agent, foaming agent, silicone oil and diisocyanate in step S5 is 10:2-3:0.01-0.015:0.2-0.5:1.5-2:1-2:9-11, the temperature of the heating, stirring and mixing is 50-60°C, the temperature of the heating and aging is 110-130°C, and the time is 3-5h.

7. The preparation method according to claim 1, characterized in that: The polyether polyol is selected from at least one of bisphenol A diethanol ether, polytrimethylene ether glycol, polytetramethylene glycol, tetramethylene oxide copolymer glycol, and polyoxypropylene glycol; the catalyst is a Raney nickel catalyst; the foaming agent is n-hexane; the diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, aliphatic isocyanate, 1,5-naphthalene diisocyanate, xylene diisocyanate, and tetramethyl-m-xylene diisocyanate; and the antistatic agent is carbon black.

8. A polyurethane material for spraying and plugging air leakage in coal mines, prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A fire-resistant, leak-proof, and fire-extinguishing sprayable material for coal mines with excellent flame-retardant properties and its preparation method.

    CN103388486B

  • A bionic self-healing material for air leakage plugging in coal mines

    CN104909636B

  • Flame-retardant polyurea for new energy battery box and preparation method of flame-retardant polyurea

    CN114656828A

  • Preparation method of polymyxin B sulfate dry powder

    CN115300607A